Optimalisasi Penggunaan Game Dalam Pembelajaran Kosa Kata Bahasa Inggris Pada Anak Panti Asuhan Nurul Jannah NW - Hastuti, Hilda; Syahid, Agus; Alfilail, Nur (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
Vocabulary is one element of language that must be learned. Learning vocabulary is the most important thing in learning English. As we know that vocabulary is the basic of communication which is very necessary. The use of interesting learning media and aims to make students more motivated in learning. Charades Games is the learning strategy can be used in this activities. This game makes learning more interesting because it makes students more active in learning English. The aim of the implementing charades game as media in learning is to increase students’ vocabulary mastery and makes student more interest and fun in learning process. As the result of implementing charades games in learning vocabulary in Nurul Jannah NW Ampenan orphanage children, Mataram City shows that the students are taught to work in teams, solve the problems with team, and charades games is one of the appropriate game to teach and learn vocabulary, especially in teaching and learning Nouns. Additionally, charades games can be played without considering age boundaries.